CEH v9 certified ethical hacker version 9 : practice tests - Blockmon, Raymond (Sybex, 2016)
CEH: Certified Ethical Hacker Version 9 Practice Tests are the ideal preparation for this high-stakes exam. Five complete, unique practice tests are designed to help you identify weak spots in your understanding, so you can direct your preparation efforts efficiently and gain the confidence-and skills-you need to pass. These tests cover all five sections of the exam, allowing you to test your knowledge of Assessment; Security; Tools and Systems; Procedures and Methodology; and Regulation, Policy, and Ethics. Coverage aligns with CEH version 9, including material on cloud, tablet, and mobile phone security and attacks, as well as the latest vulnerabilities including Heartbleed, shellshock, and Poodle. The exams are designed to familiarize CEH candidates with the test format, allowing them to become more comfortable reading a Wireshark .pcap file or viewing visual depictions of network attacks. The ideal companion for the Sybex CEH v9 Study Guide, this book is an invaluable tool for anyone aspiring to this highly-regarded certification.